Keragaman Genetik Kacang Bogor (Vigna subterranea L. Verdc.) Berdasarkan Marka SSR (Simple Sequence Repeat) - Illahi, Zikril; Wiendi, Ni Made Armini; Sudarsono, dan (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTBambara groundnut (Vigna subterranea L. Verdc.) is an important underutilized legume crop in Indonesia. The aim of this research is to study genetic diversity of bambara groundnut from Sukabumi and Sumedang, West Java, Indonesia. This study used 107 bambara groundnut accessions, which consisted of 57 accessions from Sukabumi and 50 accessions from Sumedang. We use five simple sequence repeat (SSR) to analyze the accessions. Totally nine alleles were detected, with a mean of 1.8 alleles per locus. Allelic and gene diversities were higher in Sumedang (1.8 alleles per locus and 0.119) than in Sukabumi population (1.4 alleles per locus and 0.020), respectively. We constructed a phylogenic tree by Neighbor-Joining analysis based on genetic distances (DA) and showed the tree divided bambara groundnut accessions into two broad groups according to the origin of samples (Sukabumi and Sumedang). Results from the phylogenic tree are in line with those from the population structure analysis. Keywords: allele diversity, bambara groundnut, genetic distance, under utilized legume